Synthesis of Disulfanes from Organic Thiocyanates Mediated by Sodium in Silica Gel - Maurya, Chandra Kant; Mazumder, Avik; Kumar, Ajeet; Gupta, Pradeep Kumar (Synlett, 2016)
We report an efficient procedure for the synthesis of symmetrical disulfanes from organic thiocyanates in the presence of sodium in silica gel at room temperature. By avoiding the use of foul-smelling thiols, the present protocol provides an attractive alternative to existing methods for the preparation of symmetrical disulfanes.
Keywords: disulfides; reduction; thiocyanates; coupling; sodium